Benefits of Zakat in Zakat to Increase Ummah's Economic Growth - Kahar Muzakir (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article describes the benefits of zakat to increase the economic growth of the ummah. Zakat is something that is absolutely obligatory to do if it meets the requirements. The Hadith emphasizes that the people assigned to collect and allocate zakat are prepared and emphasizes that zakat must be collected, not left to the wishes of those who give zakat. Management of zakat that is organized and carried out systematically based on modern management as intended in Law Number 38 of 1999 concerning the management of zakat, which was later amended by Law Number 23 of 2011 concerning the management of Zakat, is intended so that zakat is able to make a real contribution to increasing welfare of Muslims. Today's modern economy, especially in the face of the free market era of the 2015 Asean Economic Community, of course this zakat contribution is very much needed to strengthen human resources and support the purchasing power of the Community Economy